The Effect of Sweet Potato Flour, Kabuto, and Sago on Broiler Chicken Meat Ball Quality - Nasutio, Fakhrul Arifin; Hafid, H.; Aka, R. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This study was aimed to produce processed meat of broiler chicken with a better quality andto evaluated consumer acceptability on broiler chicken meat ball Â that use white sweet potato flour,kabuto flour, and sago flour as filler. This study used Completely Randomized Design (CRD) with 3treatments and 4 replications. The treatments were the using of white sweet potato flour (B1),kabuto flour (B2), and sago flour (B3) as much as 20%. The observed parameters were physicalquality test (cooking loss and pH) organoleptic evaluation (color, shape, texture, aroma, fracturingpower, supplenes, flavour, compactness, attractiveness, and acceptability), and chemicalcomposition (water, ash, fat, and protein content) of broiler chicken meat ball. For organoleptictesting, Scoring Different test was used with 25 panelist. Result of this study showed that the usingof white sweet potato, kabuto, and sago flour did not affect cooking loss but affect the pH of broilerchicken meat ball. The using of three different flour did not affect shape, aroma, texture, falvour,fracturing power, compactness, and actractiveness, but affect the color and supplenes of broilerchicken meat ball. Broiler chicken meat ball with kabuto and sago flour were quite favored bypanelist. The result of chemical composition analysis showed that using white sweet potato, kabuto,and sago flour did not affect the protein and ash content, but affect the water and fat content ofbroiler chicken meat ball.Key Words: Meat Ball, Physical Quality, Organoleptic Quality, Chemical Quality, White Sweet PotatoÂ Flour, Kabuto Flour, Sago Flour